Clinical Picture of Craniopharyngioma in Childhood - Hamid, R; Sarkar, S; Hossain, MA; Mazumder, U; Akanda, MO; Parvin, R (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2):123-6The abstract of this article is available on the PubMed website